2009
DOI: 10.1007/s00723-009-0077-4
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the EPR Spectra in the Cytochrome bc 1 Complex from Saccharomyces cerevisiae

Abstract: Quinone molecules are ubiquitous in living organisms. They are found either within the lipid phase of the biological membrane (quinone pool) or are bound in specific binding sites within membrane-bound protein complexes. The biological function of such bound quinones is determined by their ability to be reduced and/or oxidized in two successive one-electron steps. As a result, quinones are involved as one-or two-electron donors or acceptors in a large number of biological electron-transfer steps occurring duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…sphaeroides structure, which is most pertinent to this study (Figure ). Specific mutagenesis coupled with kinetic, spectroscopic, and thermodynamic measurements to explore functional consequences had indicated that the three potential H-bonding partners shown in Figure were all important. , More recently, high-resolution EPR approaches have been used to explore the interaction between the SQ i paramagnet and nuclear spins in the immediate environment. Our own results were quite coherent with the mutagenesis studies and the structure shown; they revealed spin interaction with a N atom, with characteristics compatible with the direct H-bond to N ε of His-217 of the cyt b subunit, additional 1 H or 2 H interactions indicating a second H-bond, likely to either a water or Asp-252, and no other strong spin interaction with protein or solvent. However, structural interpretations from both crystallographic and spectroscopic approaches have been controversial, with several other suggestions for H-bonding partnerships. …”
supporting
confidence: 74%
See 1 more Smart Citation
“…sphaeroides structure, which is most pertinent to this study (Figure ). Specific mutagenesis coupled with kinetic, spectroscopic, and thermodynamic measurements to explore functional consequences had indicated that the three potential H-bonding partners shown in Figure were all important. , More recently, high-resolution EPR approaches have been used to explore the interaction between the SQ i paramagnet and nuclear spins in the immediate environment. Our own results were quite coherent with the mutagenesis studies and the structure shown; they revealed spin interaction with a N atom, with characteristics compatible with the direct H-bond to N ε of His-217 of the cyt b subunit, additional 1 H or 2 H interactions indicating a second H-bond, likely to either a water or Asp-252, and no other strong spin interaction with protein or solvent. However, structural interpretations from both crystallographic and spectroscopic approaches have been controversial, with several other suggestions for H-bonding partnerships. …”
supporting
confidence: 74%
“… 20 24 Our own results were quite coherent with the mutagenesis studies and the structure shown; they revealed spin interaction with a N atom, with characteristics compatible with the direct H-bond to N ε of His-217 of the cyt b subunit, additional 1 H or 2 H interactions indicating a second H-bond, likely to either a water or Asp-252, and no other strong spin interaction with protein or solvent. 20 22 However, structural interpretations from both crystallographic 25 30 and spectroscopic approaches 23 have been controversial, with several other suggestions for H-bonding partnerships.…”
mentioning
confidence: 99%
“…Debates about the direct coordination of histidine to semiquinones are currently occurring in other quinone containing proteins e.g. in the bc 1 complex 85,86 where the presence of an intermediate bound water molecule may explain the observed spectroscopic differences. Such a bound water molecule may also occur between Q H and His98 in WT QOX, aiding its function, while in the H98F variant a complete loss of enzymatic activity 21 is observed, which may correlate with the absence of such a bound water molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Because the arrival of the electrons is separated in time, the reaction must involve the formation of an SQ intermediate (SQ i ) that is stabilized within the Q i binding pocket before the final product (QH 2 ) is formed and leaves the site. Indeed, a stable radical signal originating from the Q i site was recognized in early EPR studies on submitochondrial particles and crude protein extracts , and has been explored since then as a key mechanistic element of models proposed for that site. ,,,,,, …”
Section: Mechanistic Insights Into the Catalytic Qi/qn Sitementioning
confidence: 99%